Partner independent fusion gene detection by multiplexed CRISPR-Cas9 enrichment and long read nanopore sequencing - Christina Stangl (Nature Portfolio, 2020)
Fusion genes are a hallmarks of cancer, though breakpoint-position promiscuity restricts diagnostic detection. Here, the authors present FUDGE, a CRISPR-Cas9-based enrichment strategy for nanopore sequencing to identify target fusions irrespective of genomic breakpoint or fusion partner.